Penerapan Model Based Testing pada Pengujian Aplikasi Kawn Subscriptions Manager - Sinaga, Arnaldo Marulitua; Hutapea, Mikhael (Universitas Nusa Cendana, 2023)
This research focuses on the Kawn Subscriptions Manager app, which was developed to help Food and Beverage (F&B) businesses manage customer subscriptions. Currently, the Kawn Subscriptions Manager application does not have a standardized test suite that has been validated. Therefore, in this research, Model-Based Testing (MBT) is applied in testing the Kawn Subscriptions Manager application as a testing method to produce a specific and technical test suite. MBT is a testing method based on the behavioral model of the system being tested. Then, to measure the adequacy of test cases generated by MBT, mutation testing is used. The model is created using the GraphWalker tool and testing is done automatically using Selenium and testNG in the Eclipse IDE text editor. From the results of the study, it is known that MBT testing generates test cases from the behavior model of the function being tested. Testing with MBT shows that no failures were found in the tested functions. Then the average mutation score is 72.18% which indicates that the test cases generated by MBT are adequate or in the medium category. However, it is important to note that while MBT was successful in generating test cases that examined the application's behavior, it was found that the method was unable to detect failures caused by mutants that did not significantly affect the application's behavior. This finding suggests that while MBT can be an effective tool for testing key functions, additional methods are needed to identify failures that may result from minor or insignificant changes to the application code.